Sol-gel BST Thin Films for FeFET Applications : Fabrication and Characterization - Ala'eddin Ahmad Jaber Saif (School of Microelectronic Engineering, 2012)
The main objective in this work is to obtain the memory behavior of the ferroelectric BST thin films when used in the metal-ferroelectric-insulator-semiconductor (MFIS) structure. Additional objectives will be to derive the fabrication details, material and electrical characteristics.